PENINGKATAN KINERJA GURU DALAM PENYUSUNAN PERANGKAT RENCANA PELAKSANAAN PEMBELAJARAN MELALUI IMPLEMENTASI SUPERVISI AKADEMIK KEPALA SEKOLAH DI SMA NEGERI 6 BENGKULU SELATAN - Tarman Hayadi (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2015)
This research is a type of Action Research School where researchers directly involved in research to provide guidance and coaching as well as observing teachers in preparing lesson plans are implemented through academic supervision in school activities. The main purpose of this action research is to investigate the implementation of the Academic Supervision Principal in an effort to improve the performance of teachers in preparing the lesson plan in SMAN 6 South Bengkulu academic year 2014/2015 is feasible and effective. Based on the results of mentoring and coaching principals and discussion on the implementation of academic supervision can be concluded that: (1) Performance of teachers in preparing lesson plans through the implementation of academic supervision activities showed an increase in each cycle. The value of teachers' performance through the implementation of academic supervision activities principals at each cycle showed an increase in results. Indicators of achievement ≥85% of teacher performance category